(untitled) - White, Michael (London, 1983)
This book introduce about perspectives on Japanese employment systems, the scope of the study, a Japanese-owned factory in its community, work and authority in a Japanese-owned factory.
Keywords: Quan hệ công nghiệp,Industrial relations; Vương quốc Anh,Great Britain